Institutionalising integrity in child care institutions: Bridging macro-level pressures and micro-level job design - Nur Rifhan A.Rahim; Nor Azimah Kamaruddin; Nur Hanisah Mohamad Razali; Nor Azairiah Fatimah Othman; Mohd Khairul Ariff Noh; Nik Dzulaikha Binti Nik Dazuki; Faten Elina Kamaruddin (Masyarakat, Kebudayaan dan Politik, 2026)
Child abuse in childcare institutions continues to be a global concern, despite the implementation of more stringent regulatory frameworks. While previous research has concentrated on compliance mechanisms and caregiver credentials, limited consideration has been devoted to how organizational integrity is institutionalized across macro and micro-level institutions. This study investigates how external institutional pressures and internal job design work together to strengthen organizational integrity in Malaysian childcare institutions. This study used a qualitative research design, and the data were analyzed thematically using Atlas.ti. This study illustrates that preventing child abuse in childcare institutions demands the institutionalization of integrity at all levels of the organization. While coercive regulatory tools are an important legal precaution, sustained integrity is fostered through micro-level job design that incorporates ethical responsibility into daily caregiving actions. By incorporating institutional theory and the job characteristics model, this study contributes to a novel macro-micro level framework that explains how integrity is established, maintained, and reinforced. The conclusion of this study demonstrates an essential institutional failure in the Malaysian context, which is the absence of a national integrity blueprint within mandatory childcare training that results in inconsistent ethical norms among institutions.